Kemampuan Laba dan Arus Kas Operasi dalam Memprediksi Arus Kas Masa Depan pada Perusahaan BUMN yang terdaftar di BEI Tahun 2016 - 2020 - Srikintan Srikintan; Mia Angelina Setiawan (Universitas Negeri Padang, 2022)
The current study aims to to achieve empirical evidence concerning the potential of net profits and cash flow operations to predict future cash flows and which ability to be taken into consideration superior in predicting future cash flows. The population are the indexed company of country -Owned organisations at the IDX in 2016 – 2020. The sampling method used the purposive sampling that produced 85 for a 5-year observation. Analysis was based on, secondary data types obtained from the legitimate website of IDX. The analysis that produced used multiple linear regression analysis. The results of this analysis imply that net profits has the ability to predict future cash flows while cash flow operastions are not longerable to predictfuture cash flows for BUMN companies at the IDX . This Assessment also indicates that the ability of net profits greater than operating cash flow to predicting future cash flows.